The observing self as a catalyst for behaviour change and wellbeing: Effective personal informatics system design to promote behaviour change in the changing health paradigm - De Villiers, Stephanie (Research of GSB, 2018)
The current study is a user-centred enquiry into how wellness-related personal informatics (PI) systems can be more effectively designed to better promote lasting behaviour change and sustained wellbeing in the context of the changing health paradigm. Until recently, the Western biomedical model with its disease focus has been effective in delivering health care; however, this paradigm does not efficiently support a system in crises - the contemporary health care system which is confronted with complex challenges of modern lifestyle diseases and behavioural disorders. Enabled by the technological revolution, a Systems Medicine model - a preventative, personalised, predictive and participatory (P4) approach - is emerging and PI systems play a significant role in realising this pre-clinical, patient-centric, behaviour-focussed shift in health care. This viewpoint paper argues that design strategies applied in PI systems to promote behaviour change play a vital role in supporting health outcomes, specifically, persuasive and mindful user experience (UX) strategies. By applying a phenomenographic research methodology, a user-centred approach is taken to understand qualitatively different ways in which PI systems (and their inherent design strategies) are experienced by users, to inform more intuitive design of PI systems that balance behaviour change strategies to support more lasting shifts and sustainable states of wellbeing. Drawing together ideas from systems medicine, complexity theory, persuasive and mindful design approaches in conjunction with phenomenography, this study aims to understand experiential nuances to offer implications for the future design of health care through PI systems. The theory built through the research process is applied in a prototype design, which is presented as an example of a PI system design that balances persuasive and mindful strategies and aims to promote lasting behaviour change and enduring states of wellbeing more effectively.